Vetting of Bloomberg’s ESG Governance ISS:QualityScore [GQS] - Lusk, Edward J.; Wells, Mia (Archives of Business Research, 2021)
Context Of the plethora of market navigation platforms, the Environment, Social, and Governance [ESGÓ]-platform offered by BloombergÔ Professional Services* is one of the most richly endowed, including nearly 2,000 data-fields that provide an invaluable context for better understanding the “Stakeholder-impact” of the firm’s activities. A recent amelioration of the ESG-platform is the link with Institutional Shareholder Services [ISS] that offers a taxonomy where firms are assigned to Governance-risk decile-groups based upon ISS:GovernanceQualityScores: (GQSÔ). The GQS-platform offers a data-driven approach to scoring & screening designed to help investors monitor company governance activities so as to better inform their decision-making. Study Design Clear is: Market Intel-Platforms only have one simple raison d’être: To provide a relative advantage in teasing out market winners relative to the “Squawk-On-The Street”. If this is the case, information professionals, in a best practices context, are tacitly obligated to offer vetting tests of platforms such as the GQS to service investors in need an independent and reliable evaluation to Ferret-out useful market guidance platforms. In this endeavor, we offer a vetting evaluation of a random sample of firms included in the two polar-ISS:GQS:Classifications: GQS[1] & GQS[10]]. Point of information The intent of the GQS-Vetting is not to “reverse-engineer” the results of the GQS-assignment protocol so as to arrive an “inferentially” de-coded approximation of the actual ISS:GQS-protocol. Our vetting addresses the question: Is there a logical reason to reject the belief that the set of GQS-assignment protocols are not well formed thus creating Governance-risk-groupings that have no intra-group coherence and so exhibit no inter-group differentiability. Results Initially, we used a Strawman-Vetting test followed by FPE-inferential tests using specific and sensitive Income Statement and Balance Sheet Panel-profiles from a random sample of the firms in: GQS[1] & GQS[10]. We find that the triage-focus of GQS[1] is “Revenue at the Margin” while that of GQS[10] is “Asset[Net] Management”. Also, both groups have exhibited impressive attention to managing Working Capital. Summary: The ISS:GQS-assignment protocols seem to be well-formed and capable of offering useful differentiation.